Upaya Peningkatan Motivasi dan Keaktifan Belajar Murid Melalui Penarapan Model Kooperatif Tipe Numbered Heads Together di Kelas XE8 di SMA N 2 Bukittinggi - Syifa Dwi Rahma; Heffi Alberida; Oktafianti Oktafianti (Yayasan Tajuk Indonesia, 2025)
Low motivation and activity hinders Biology leraning achievement. This condition was evident from the pre-cycle observation in class X E8 of SMA Negeri 2 Bukittinggi, the data shows that students learning motivation only reaches 56% and learning activity is 44,4%. This study aims to examine the effectiveness of implementing the cooperative learning model type Numbered Heads Together (NHT) in improving students’ motivation and activeness. The research was conducted using Classroom Action Research (CAR) with the Kemmis and McTaggart model through two cycles, involving 36 students. Data were collected through motivation questionnaires and observation sheets of learning activeness, then analyzed using descriptive quantitative methods. The results showed an increase in learning motivation from 63.9% in cycle I to 83.3% in cycle II, and an increase in learning activeness from 66.6% in cycle I to 88.8% in cycle II. These findings indicate that the NHT model is effective in enhancing students’ motivation and activeness, and can be applied as an innovative, interactive, and collaborative approach in biology learning.